The Influence of Green Accounting Implementation on Financial Reporting Transparency as well as Corporate Social and Environmental Responsibility in Modern Companies - Jaka Darmawan; Andam Dewi Syarif; Yimmi Syavardie; Donny Wijaya (Mandalika Institute, 2026)
This study addresses the problem that corporate claims of environmental responsibility are often insufficiently verifiable due to limited financial reporting transparency in modern companies. The objective is to examine whether Green Accounting Implementation influences Financial Reporting Transparency and whether transparency strengthens Corporate Social and Environmental Responsibility outcomes. The study employs a literature-based research design using content analysis to synthesize evidence from scholarly sources on green accounting practices, transparency mechanisms, and CSR/environmental responsibility credibility. The data consist of relevant written literature that describes implementation processes, transparency qualities, and accountability-related reporting expectations, enabling the identification of recurring patterns across the three focal constructs. The study concludes that Green Accounting Implementation improves the transparency of financial reporting by strengthening the structured production and traceability of environmental-related information. In turn, improved transparency increases the credibility of corporate social and environmental responsibility by allowing stakeholders to evaluate commitments using more verifiable evidence.